Variable regions of the glyS, infB and rplB genes usable as novel genetic markers for identification and phylogenetic purposes of genera belonging to the family Propionibacteriaceae - Mekadim, C; Killer, J; Pechar, R; Mrázek, J (International journal of systematic and evolutionary microbiology, 2018)
No common, unique genetic markers applicable to classification and phylogenetics for significant genera within the Propionibacteriaceae family have been suggested yet. Therefore, the aim of the study was to propose those genes in the genera Acidipropionibacterium, Cutibacterium, Propionibacterium and Pseudopropionibacterium. These genera were recently elicited from the genus Propionibacterium through whole genomic analyses. Three housekeeping genes, glyS, infB and rplB, were selected from many others according to the requirements for appropriate classification/phylogenetic markers. Concrete fragments of the genes were amplified using specific primers in most of the type (14) and 11 wild strains (originating from dairy products, human skin and the crop of a laying hen) recently classified into the genus Propionibacterium. Sequences obtained from amplicons were used to perform gene statistics and phylogenetic analyses with respect to applicability in classification, typing and phylogeny. The 16S rRNA gene sequences, still considered relevant in spite of its proven shortcomings as a basic tool for evaluation of bacterial phylogeny, were used as a baseline for comparative analyses. The statistics of the gene sequences revealed that the variable regions of all three genes have higher resolution capabilities among strains examined compared to the 16S rRNA gene analysis. Phylogenetic analyses based on individual gene sequences and their concatenate enabled to distinguish clusters of species belonging to the genera Acidipropionibacterium, Cutibacterium and Propionibacterium, which corresponds with a recently reported genomic study. Thus, the crucial importance of this study is the economically advantageous classification and typing of propionibacterial isolates and strains through the three gene regions in contrast to the requirement for whole genomic assays.
Keywords: kur domácí; Phylogeny; Dairy Products; Chickens; DNA, Bacterial; Genetic Markers; RNA, Ribosomal, 16S; Humans; Propionibacterium; zvířata; Sequence Analysis, DNA; techniky typizace bakterií; Propionibacteriaceae; RNA ribozomální 16S; classification; DNA bakterií; phylogenetics; mléčné výrobky; Genes, Bacterial; glyS, infB and rplB genes; ženské pohlaví; sekvenční analýza DNA; Animals; lidé; bakteriální geny; genetické markery; fylogeneze; Bacterial Typing Techniques; Female